Empowering university waste management awareness and action with a prototype web application for sustainable change - Regar Cheryl Lidia; Suryatiningsih Suryatiningsih; Budiwati Sari Dewi (E3S Web of Conferences)
The challenge of waste management in Indonesia is a pressing environmental issue, exacerbated by the substantial waste output of institutions like Telkom University Bandung. To tackle this issue, we developed a comprehensive web-based information system aimed at optimizing waste management practices within the university context. Utilizing cutting-edge technology and innovative methodologies, our system offers real-time monitoring, precise data recording, and incentives for waste segregation. In this study, we not only focused on the development of the system but also conducted a comparative analysis involving three other waste management applications, each employing different methodologies. Our findings indicate a promising response to our system, with 68.5% of participants acknowledging its potential efficacy in transforming waste management practices. However, it’s essential to recognize that waste management is a multifaceted issue requiring a collaborative effort. Thus, future endeavors will involve not only the implementation of our system within Telkom University but also active engagement with the university community and stakeholders. Furthermore, we plan to pilot the system, establish volunteer programs, and foster partnerships to ensure its long-term success and sustainability. By integrating technology, community participation, and strategic collaborations, our initiative aims to instill a waste-free culture not only within Telkom University but also across other academic institutions in Indonesia. Ultimately, our goal is to contribute to the national objective of achieving zero waste and promoting environmental sustainability.